New therapeutics beyond amyloid-β and tau for the treatment of Alzheimer’s disease - Zhang, Feng; Zhong, Rujia; Cheng, Cheng; Li, Song; Le, Wei-dong (Acta pharmacologica Sinica, 2021)
As the population ages, Alzheimer’s disease (AD), the most common neurodegenerative disease in elderly people, will impose social and economic burdens to the world. Currently approved drugs for the treatment of AD including cholinesterase inhibitors (donepezil, rivastigmine, and galantamine) and an N-methyl-D-aspartic acid receptor antagonist (memantine) are symptomatic but poorly affect the progression of the disease. In recent decades, the concept of amyloid-β (Aβ) cascade and tau hyperphosphorylation leading to AD has dominated AD drug development. However, pharmacotherapies targeting Aβ and tau have limited success. It is generally believed that AD is caused by multiple pathological processes resulting from Aβ abnormality, tau phosphorylation, neuroinflammation, neurotransmitter dysregulation, and oxidative stress. In this review we updated the recent development of new therapeutics that regulate neurotransmitters, inflammation, lipid metabolism, autophagy, microbiota, circadian rhythm, and disease-modified genes for AD in preclinical research and clinical trials. It is to emphasize the importance of early diagnosis and multiple-target intervention, which may provide a promising outcome for AD treatment.
Veröffentlicht: 02. Dezember 2020
Gesehen am 29.02.2024